Implementasi Project Based Learning Terhadap Kemampuan Berpikir Kritis Siswa pada Prmbelajaran IPS Kelas IV SDN 1 Sedyo Mulyo - Leni Maryani; Mega Kusuma Putri; Hetilaniar (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the implementation of Project Based Learning (PjBL) and to examine students’ critical thinking skills in fourth-grade Social Studies learning at SDN 1 Sedyo Mulyo. This study employed a descriptive qualitative method aimed at providing an in-depth description of the implementation process of project-based learning in teaching and learning activities. The research subjects consisted of 33 students, including 18 male students and 15 female students. Data collection techniques were carried out through observation, interviews, documentation, and field notes. The data analysis technique used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was obtained through source triangulation and technique triangulation. The results showed that the implementation of Project Based Learning was carried out effectively through project activities such as creating concept maps and compiling clippings about social problems in the surrounding environment. The implementation of this model was able to increase student engagement in the learning process, such as active participation in discussions, the ability to express opinions, and collaboration among students in completing projects. In addition, students demonstrated better critical thinking skills in analyzing social problems found in their environment. Therefore, it can be concluded that Project Based Learning is effectively applied in Social Studies learning because it is able to create an active and collaborative learning atmosphere and encourage the development of critical thinking skills among fourth-grade students at SDN 1 Sedyo Mulyo.